2009
DOI: 10.1002/zoo.20255
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary exposure of some western‐hemisphere snake and lizard species to ultraviolet‐B radiation in the field: how much ultraviolet‐B should a lizard or snake receive in captivity?

Abstract: Studies of voluntary exposure to ultraviolet-B (UVB) radiation from the sun in the field were conducted in the southern US and Jamaica for 15 species of lizards and snakes occupying various habitats. Species were sorted into four zones of UVB exposure ranging from a median UV index of 0.35 for zone 1 to 3.1 for zone 4. Guidelines for UVB exposure in captivity of these and species occupying similar light environments are presented. Data for most species were collected during mid-day during the spring breeding s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 34 publications
2
36
0
Order By: Relevance
“…Bennett () carried out a study on six chameleon species in Kenya and found all to be capable thermoregulators, moving to high sun‐exposed positions to reach an optimal thermal limit during the day. Such thermoregulatory behavior can result in a daily pattern of UV exposure in lizards, where high levels of UV are received up until a thermal limit is reached and animals retreat from full sun (Ferguson et al, ). In our study, we did not find evidence of a thermal limit in C. brevicorne or C. nasutum , but because we measured ambient air temperature in shade near chameleons rather than actual body temperature we may have been unable to detect such thermal preferences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bennett () carried out a study on six chameleon species in Kenya and found all to be capable thermoregulators, moving to high sun‐exposed positions to reach an optimal thermal limit during the day. Such thermoregulatory behavior can result in a daily pattern of UV exposure in lizards, where high levels of UV are received up until a thermal limit is reached and animals retreat from full sun (Ferguson et al, ). In our study, we did not find evidence of a thermal limit in C. brevicorne or C. nasutum , but because we measured ambient air temperature in shade near chameleons rather than actual body temperature we may have been unable to detect such thermal preferences.…”
Section: Discussionmentioning
confidence: 99%
“…Some data on exposure to UV‐B radiation in wild reptiles has been collected by Ferguson et al who measured UV‐B radiation levels in the field for more than 15 North American species (Ferguson et al, ; Ferguson, Brinker, & Gehrmann, ; Ferguson, Gehrmann, Brinker, & Kroh, ; Ferguson, Gehrmann, Brinker, Kroh, & Ruthven, ; Ferguson, Gehrmann, Karsten et al, ). To facilitate the application of these findings to a broader array of captive reptile species, four UV‐B zones were defined to categorize species based on the amount of available UV‐B measured and the ecological traits of each species (Table ; Ferguson et al, ). Recent work by the British and Irish Association of Zoos and Aquariums referred to these zones as the “Ferguson Zones” and developed the “UV‐Tool” (Baines et al, ), which groups over 250 species of reptiles and amphibians into the four Zones based on species behavior, habitat preference, and thermal requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Tortoises housed indoors (self-ballasted mercury-vapor lamp and fluorescent UVB-emitting lamp groups) were placed in open-top plastic boxes a (vivariums; 120 X 60 X 18.5 cm). 9 To determine variations in amount of UVB radiation at the basking areas in the enclosures during the daytime, measurements were obtained every 30 minutes on days 0 and 35 and mean ± range values were calculated. That lamp was oriented vertically and placed 30 cm above the floor of 1 side of the box, in accordance with the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…6 The importance of vitamin D 3 in reptiles is indicated by results of studies [7][8][9] in which captive and wild reptiles voluntarily exposed themselves to UVB radiation. 6 The importance of vitamin D 3 in reptiles is indicated by results of studies [7][8][9] in which captive and wild reptiles voluntarily exposed themselves to UVB radiation.…”
mentioning
confidence: 99%
“…Each compartment was furnished with a paper substrate, a basking log, heat lamps, and a UV light (Exo-Terra ReptiGlo 10.0 Compact Fluorescent Terrarium Bulb 13W, Rolf C. Hagen, Inc., Mansfield, MA) so that females could perceive male color badges under lighting conditions approximating those experienced in nature (Bennett et al 1994;Ferguson et al 2010). The arena was cleaned with soap and water between trials to remove any olfactory cues.…”
Section: Mate Choice Trialsmentioning
confidence: 99%